Diagnostic accuracy of echocardiography for pulmonary hypertension: a systematic review and meta-analysis. Issue 8 (25th February 2011) - Janda, Surinder; Shahidi, Neal; Gin, Kenneth; Swiston, John
Abstract : Context: Right heart catheterisation is the gold standard for the diagnosis of pulmonary hypertension. However, echocardiography is frequently used to screen for this disease and monitor progression over time because it is non-invasive, widely available and relatively inexpensive. Objective: To perform a systematic review and quantitative meta-analysis to determine the correlation of pulmonary pressures obtained by echocardiography versus right heart catheterisation and to determine the diagnostic accuracy of echocardiography for pulmonary hypertension. Data sources: MEDLINE, EMBASE, PapersFirst, the Cochrane collaboration and the Cochrane Register of controlled trials were searched and were inclusive as of February 2010. Study selection: Studies were only included if a correlation coefficient or the absolute number of true-positive, false-negative, true-negative and false-positive observations was available, and the 'reference standards' were described clearly. Data extraction: Two reviewers independently extracted the data from each study. Quality was assessed with the quality assessment for diagnostic accuracy studies. A random effects model was used to obtain a summary correlation coefficient and the bivariate model for diagnostic metaanalysis was used to obtain summary sensitivity and specificity values. Results: 29 studies were included in the meta-analysis. The summary correlation coefficient between systolic pulmonary arterial pressure estimated from echocardiography versus measured by right heart catheterisation was 0.70 (95% CI 0.67 to 0.73; n=27). The summary sensitivity and specificity for echocardiography for diagnosing pulmonary hypertension was 83% (95% CI 73 to 90) and 72% (95% CI 53 to 85; n=12), respectively. The summary diagnostic OR was 13 (95% CI 5 to 31). Conclusions: Echocardiography is a useful and noninvasive modality for initial measurement of pulmonary pressures but due to limitations, right heart catheterisation should be used for diagnosing and monitoring pulmonary hypertension.